Comparative evaluation of the surface tension and the pH of calcium hydroxide mixed with five different vehicles:An in vitro study - Poorni S; Miglani Revathi; Srinivasan M; Indira R (Wolters Kluwer Medknow Publications, 2009)
Aim: The aim of this study was to evaluate the surface tension and pH of five different vehicles that are used as potential agents to mix calcium hydroxide in root canal treatments and to compare them with the final surface tension and pH of calcium hydroxide mixed with these vehicles. Materials and Methods: The study was carried out in two phases. In Phase I, the surface tension and pH of five vehicles (distilled water, saline, anesthetic solution, chlorhexidine, and glycerin) were evaluated using a Du Nuoy Tensiometer and a pH Meter. In Phase II, a predetermined amount of calcium hydroxide was mixed with the individual vehicles and the surface tension and pH was determined. In each group, seven samples were evaluated. Results: Among the individual vehicles, chlorhexidine had the least surface tension values (39.8+1.1 dynes/cm). Among the various calcium hydroxide mixtures, calcium hydroxide with chlorhexidine showed the least surface tension values (36.4+1.1 dynes/cm). All the vehicles showed an acidic pH ranging from 5 to 6.5. There was a significant increase in the pH values with the addition of calcium hydroxide to the respective vehicles. The calcium hydroxide mixtures had an alkaline pH ranging from 9 to 11.5; the highest pH was observed for calcium hydroxide mixed with distilled water and saline (11.5+0.2). Conclusion: The surface tension and pH of the vehicles directly influenced the surface tension and pH of the calcium hydroxide mixtures. Chlorhexidine was found to be a better vehicle for calcium hydroxide when used as an intracanal medicament.